Penyelesaian Sengketa Wanprestasi Pada Perjanjian Kerjasama (Ijarah) Antara Pengusaha Dengan Pengrajin Batik Di Kota Pekalongan - Najib, Moh Ainun; Sofiani, Trianah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The failure of batik craftsmen to produce quality products results in bad quality products that are detrimental to entrepreneurs and reduce the profits obtained in product distribution in the market. This condition makes batik entrepreneurs ask for compensation payments to batik craftsmen. However, most batik craftsmen do not pay losses for various reasons, causing problems between the two parties. This study examines the causes of default and its resolution when there is bad faith from Batik craftsmen. The research method uses empirical juridical with a qualitative approach. Data collection techniques use observation, interviews, and document studies. The analysis technique uses a flow model. The results of the study show that the factors causing craftsmen to lack good faith are that they want to avoid responsibility, and the amount of losses that must be paid is too high, so they are unable to pay it. The settlement between entrepreneurs and Batik craftsmen was carried out through deliberation. The results of deliberation between entrepreneurs and craftsmen usually to paying compensation in installments and reducing the amount of Compensation that must be paid